IDENTIFIKASI POLIMORFISME GEN GH (GROWTH HORMONE) SAPI BALI DENGAN METODE PCR-RFLP - Sri Rahayu; SB Sumitro; T Susilawati; Soemarno Soemarno (The East Java Biological Society, 2006)
This study was conducted to identify polymorphism of growth hormone gene of Bali cattle. A PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) procedure was developed for determining polymorphism of growth hormone gene. The DNA was isolated from blood samples by salting out method. Total DNA were amplified with forward primer, 5’-TAGGGGAGGGTGGAAAATGGA-3’ and reverse primer, 5’-GACACCTACTCAGACAATGCG-3’. The PCR product was digested by HaeIII restriction enzyme. Result of the amplification was a specific single band with fragment 450 bp. Restriction with HaeIII restriction enzyme resulted four kinds of haplotype. Haplotype I was not cut by HaeIII restriction enzyme. Haplotype II were cut into two, 225 bp and 150 bp,. Haplotype III were cut into three size, 400 bp, 225 bp and 150 bp. Haplotype IV were cut into five fragments 450 bp, 400 bp, 275 bp, 225 bp and 150 bp.